THEORETICAL PRINCIPLES OF MANAGEMENT ACCOUNTING, AUDITING AND DIGITAL RESEARCH IN FRUIT AND VEGETABLE PROCESSING ENTERPRISES - Rahmatullaev Mirjalol Khatam ogli (Scholar Express Journals, 2026)
This article discusses the theoretical and practical aspects of improving management accounting, determining financial results and using digital technologies in audit processes at fruit and vegetable processing enterprises. The study analyzes the effectiveness of the management accounting system, cost accounting and analysis of financial results at fruit and vegetable processing enterprises
Keywords: management accounting; fruit and vegetable processing; financial results